2012
DOI: 10.1111/j.1399-3038.2012.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to goat’s and sheep’s milk in a population of cow’s milk–allergic children treated with oral immunotherapy*

Abstract: We found a high prevalence (26%) of allergy to GSM in our population of CM-allergic children treated with oral immunotherapy. Therefore, tolerance to GSM should be assessed in order to provide accurate nutritional advice and minimize life-threatening accidental intake. Specific IgE to CM casein, goat's and sheep's whole milk is a good marker of this allergy. Although CM oral immunotherapy is a specific treatment for CM allergy, it may not be effective against allergy to the milk of other mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 17 publications
0
20
0
3
Order By: Relevance
“…Several case reports on allergy to goat and sheep milk proteins in individuals previously desensitized to CM can be found in the literature 2627. In fact, Rodríguez del Río et al28 found, in patients who tolerated CM after CM-OIT, that 26% of them were still allergic to goat's milk and ewe's milk, with 47% of the positive oral food challenges graded as anaphylactic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports on allergy to goat and sheep milk proteins in individuals previously desensitized to CM can be found in the literature 2627. In fact, Rodríguez del Río et al28 found, in patients who tolerated CM after CM-OIT, that 26% of them were still allergic to goat's milk and ewe's milk, with 47% of the positive oral food challenges graded as anaphylactic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…With a mean age of 6 years, GM‐allergic/CM‐tolerant patients are generally older than those presenting CMA and their symptoms are more frequently severe . A recent study reported a high prevalence (26%) of allergy to goat's and/or sheep's milk (SM) in a population of CM‐allergic children treated with CM oral immunotherapy, as confirmed by a controlled positive oral challenge, which led to an anaphylactic reaction for almost half of the GM‐/SM‐allergic patients .…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is essential from a clinical stand point, as many children with cow’s milk allergy react also to goat’s or sheep’s milk. Unfortunately, orally induced tolerance to cow’s milk does not protect these children from reactions to the milk of other mammals [109,110] and elimination diets are sometime not sufficient to avoid severe reactions in allergic children [111]. A few children with severe food allergies cannot be treated with SOTI, as they do not tolerate even minute amount of the relevant allergen.…”
Section: Monitoring and Controlmentioning
confidence: 99%